PEMBELAJARAN AQIDAH AKHLAK DALAM PERSPEKTIF HUMANISME DI MA MIFTAHUL QULUB GALIS PAMEKASAN - Supandi Supandi; Ahmad Ahmad (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2019)
This study departs from a number of educational problems that present the view to researchers that it is not only the matter of material and learning facilities that leaves many problems, but the problem of delivery methods and social regulation of education which raises many problems, so researchers initiated to conduct this research. This research method uses a qualitative approach, with a naturalistic phenomenological design, by conducting descriptive studies. Implementation of moral learning in the perspective of humanism include: 1) aims to increase the potential of students intrinsically and extrinsically, 2) learning that views students as human beings are the same with each other, 3) a spirit that can be paired with a variety of learning methods. Obstacles to moral learning in humanism are: 1) too far in terms of communication, 2) student delinquency is a problem for teachers, 3) the influence of students on others. Alternative solutions include: 1) The teacher provides continuous understanding so that students, 2) teachers and education practitioners make learning innovations, 3) equips with a variety of learning media that students can be interested in learning